2021
DOI: 10.1186/s12879-021-06822-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of COVID-19 during the first 7 months of the epidemic in Vietnam

Abstract: Background Understanding the spatiotemporal distribution of emerging infectious diseases is crucial for implementation of control measures. In the first 7 months from the occurrence of COVID-19 pandemic, Vietnam has documented comparatively few cases of COVID-19. Understanding the spatiotemporal distribution of these cases may contribute to development of global countermeasures. Methods We assessed the spatiotemporal distribution of COVID-19 from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In Vietnam, the number of COVID-19 cases was relatively small, with no deaths, during the first 7 months of the pandemic. In contrast, over 4.3 million and 2.5 million cases, respectively, were reported in the United States and Brazil, with a case fatality rate of approximately 3.5% in both countries [2,3]. However, following an epidemic in summer 2021, the second year of the pandemic, the cumulative number of COVID-19 cases in Vietnam increased rapidly, reaching over 961,000 cases by the 1 st November, 2021, particularly owing to the emergence of the B.1.617.2 (Delta) variant of SARS-CoV-2 [4,5].…”
Section: Introductionmentioning
confidence: 96%
“…In Vietnam, the number of COVID-19 cases was relatively small, with no deaths, during the first 7 months of the pandemic. In contrast, over 4.3 million and 2.5 million cases, respectively, were reported in the United States and Brazil, with a case fatality rate of approximately 3.5% in both countries [2,3]. However, following an epidemic in summer 2021, the second year of the pandemic, the cumulative number of COVID-19 cases in Vietnam increased rapidly, reaching over 961,000 cases by the 1 st November, 2021, particularly owing to the emergence of the B.1.617.2 (Delta) variant of SARS-CoV-2 [4,5].…”
Section: Introductionmentioning
confidence: 96%
“…Our results indicated that easing restrictions could lead to long-term existence of high-risk clusters and recurrent high risk in certain districts. Furthermore, previous studies on modeling linkages between NPIs and COVID-19 transmission were generally retrospective or predictive analyses and often focused on a single country [ 62 - 66 ]. The advantage of this study over prior works is that we provided a novel insight for timely and cross-nation surveillance of the dynamics and characteristics of the Delta variant at the district level in SEA.…”
Section: Discussionmentioning
confidence: 99%
“…Neighbouring countries, such as Laos, Thailand, and Vietnam, also had low incidences of COVID-19 cases due to the quick implementation of countermeasures and efficient screening and isolation of confirmed cases, similar to measures taken in Cambodia ( Issac et al. 2021 ; Manabe et al. 2021 ; Phonvisay et al.…”
Section: Discussionmentioning
confidence: 99%